Child with cerebral palsy: what’s the impact on caregiver’s life? - Cristiane Xavier Silva; Édva Duarte Brito; Francisco Stélio de Sousa; Inacia Sátiro Xavier de França (Rev Rene)
This study aimed to investigate the impact that the birth of a child with Cerebral Palsy (CP) causes in the caregivers’ lives. It is a qualitative-descriptive study performed with seven female caregivers of children with CP. It was used a semi-structured interview with thematic content analysis. There was a family crisis due to the birth of children with CP. The family interaction with the child improved after obtaining further information about their health. The caregivers take pro-active role in the rehabilitation process of the child. They learn to overlook the stigma attributed to their children, but face injuries to their health and difficulties in different sectors, such as: financial difficulties and to lead their children to the rehabilitation service because of incipient offer of inter-municipal transportation. The conclusion is that CP is a psychomotor condition which is not properly understood by parents and family of CP children. Health professionals need to provide greater information about the pathology and care of children with CP, and a social support network is required.